Hubungan Antara Dimensi Lebar Induk Dengan Pedet Pada Sapi Bali (THE CORRELATION OF COW WIDTH DIMENSIONS WITH CALF OF BALI CATTLE) - Mahardika, I Putu Windhu; Sampurna, I Putu; Nindhia, Tjok Sari (Buletin Veteriner Udayana, 2015)
This research was carried out to determine the relationship between the parent widthdimension to the width dimension of Bali cattle and calves on how big the size of the widthdimension of the parent affect the pedetnya. Research object that is used consists of 20 breedingcalves and 20 calves each of 10 male and 10 female newborn calves reared by farmers in thevillage Getasan, District evening, Badung regency. To find out if there is a difference between thewidth dimension of male calves with calf female test T. sizes width dimension parent and calfwidth dimensions were analyzed using linear regression. There is no difference in the size of thewidth dimension calf cattle cow bali bali male with female. And there is a relationship between thewidth dimension of the cow bali with pedetnya and there is a difference between the ratio of thewidth dimension of each parent with a calf.
Keywords: width dimensions; cow; calf; bali cattle